Healthcare costs and utilization associated with muscle weakness diagnosis codes in patients with chronic obstructive pulmonary disease: a United States claims analysis. (3rd April 2019) - Trantham, Laurel; Sikirica, Mirko V.; Candrilli, Sean D.; Benson, Victoria S.; Mohan, Divya; Neil, David; Joshi, Ashish V.
Abstract: Aims: Muscle weakness (MW)-attributable healthcare resource utilization (HCRU) and costs in patients with chronic obstructive pulmonary disease (COPD) have not been well-characterized in US insurance claims databases. The primary objective of this study was to estimate HCRU in patients with evidence of COPD with and without MW diagnosis codes. Materials and methods: This retrospective analysis used the MarketScan ® Commercial Claims and Encounters and Medicare Supplemental and Coordination of Benefits databases. Between January 2007 and March 2016, we identified patients aged ≥40 years with diagnosis codes for COPD (≥1 emergency department or inpatient claim or ≥2 outpatient claims within 1 year). The cohort was divided into patients with and without ≥1 MW diagnosis code. Propensity score matching was used to generate pairs of patients with and without MW (1:1). Multivariable regression analyses were used to estimate adjusted incremental costs and utilization attributable to the presence of MW diagnosis codes among patients with COPD. Results: Of 427, 131 patients who met the study inclusion criteria, 14% had evidence of MW. After matching, 107, 420 unique patients remained equally distributed across MW status. Patients with MW diagnosis codes had greater predicted annual HCRU, 2, 465 greater total predicted annual COPD-related costs, and 15, 179 greater total all-cause costs than those without MW diagnosis codes. Overall, <1% of patients received COPD-related pulmonary rehabilitation services. Limitations: Study limitations include the potential for undercoding of MW and lack of information on severity of MW in claims data. Conclusion: The presence of MW diagnosis codes yielded higher HCRU in this COPD population and suggests that the burden of MW affects both all-cause and COPD-related care. However, utilization of pulmonary rehabilitation, a known effective treatment for MW, remains low. Future research should expand on our results by assessing data sources that allow for clinical confirmation of MW among patients with COPD.